Research excellence: the imperative primers - Syed Hassan, Syed Tajuddin; Mohd Elias, Saliza; Jalalian, Mehrdad (Knowledge Kingdom, 2017)
Research excellence characteristics are comprehensively delineated, encompassing creativity through transnationality and translation-capability. The research iterative primers of “Re” and “search” as the underlying push-engine, is briefly illustrated. Subsequently, a visual model depicting three major modules of the entire research tasking-process illustrates the need to balance the preparation and the rendition of data and interpretation components, through the mediating role of data capture. Traits of the primers characterising research excellence are consequently deliberated and discussed thoroughly using the acronym R-E-S-E-A-R-C-H. The initial three entities, RES, fittingly portray the literature review matrix; with reviewing of references through examining “slacks” or gaps in available literature. The E is then envisaged as representing exclusivity through ethical considerations; A as audience through imbibition of overt and covert objectives, to audit trail analysis; R as rationale through research frame (interpretive, analytical, simulative); C as encompassing creativity through coherence (tone, voice, style); and, H as the human factors-trailing from biases through needs/wants to influences. Optimising values of these primers are deemed imperative to achieve excellence in a research project process and outcome.